PENGARUH FINANCIAL SLACK TERHADAP KINERJA PERUSAHAAN STUDI PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TELAH GO PUBLIC DI BURSA EFEK INDONESIA - Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2015)
The relationship between financial slack with the company's performance is not clear. Therefore, this issue more interesting to study. Financial slack can be grouped into two types: available slack and potential slack. Therefore, this study is intended to clarify the effect of available slack and potential slack to company performance. To achieve this aim, used a linear regression equation. The study focused on companies listed on Indonesia Stock Exchange by using purposive sampling technique in sampling research so that the sample size were 112 companies. The data used in this research is secondary data with observations in the period 2008-2010. To explain the effect of financial slack on the performance of companies used the t and F test with Î± by 10 percent. Based on the analysis and discussion, some conclusions as follows: Firstly, available slack and potential slack have significant negative effect on the performance of the company. Second, the greater the slack of the company, there is a tendency that corporate leaders will tend to use the slack to fulfill its interests. Based on the above conclusions, some suggestions as follows: Firstly, if the company's performance would be improved, financial slack needs to be lowered to a level that is needed. Second, the results of this study can be used as a basis for regulators to make regulations to improve the quality of corporate governance of the corporation. Third, further research is needed by differentiating the sample of companies over companies that implement good corporate governance and corporate governance is not good.